Fatigue monitoring in high performance sport: A survey of current trends - Taylor, K.-L.; Chapman, D. W.; Cronin, J. B.; Newton, M. J.; Gill, N. (Journal of Australian Strength and Conditioning, 2012)
Research has identified a plethora of physiological, biochemical, psychological and performance markers that help inform coaching staff about when an athlete is in a state of fatigue or recovery. However use of such markers in the regular high performance training environment remains undocumented. To establish current best practice methods for training monitoring, 100 participants involved in coaching or sport science support roles in a variety of high performance sports programs were invited to participate in an online survey. The response rate was 55% with results indicating 91% of respondents implemented some form of training monitoring system. A majority of respondents (70%) indicated there was an equal focus between load quantification and the monitoring of fatigue and recovery within their training monitoring system. Interestingly, 20% of participants indicated the focus was solely on load quantification, while 10% solely monitored the fatigue/recovery process. Respondents reported that the aims of their monitoring systems were to prevent overtraining (22%), reduce injuries (29%), monitor the effectiveness of training programs (27%), and ensure maintenance of performance throughout competitive periods (22%). A variety of methods were used to achieve this, based mainly on experiential evidence rather than replication of methods used in scientific publications. Of the methods identified for monitoring fatigue and recovery responses, self-report questionnaires (84%) and practical tests of maximal neuromuscular performance (61%) were the most commonly utilised.